2017
DOI: 10.1159/000477173
|View full text |Cite
|
Sign up to set email alerts
|

Less Fibrotic Burden Differently Affects the Long-Term Outcomes of Hepatocellular Carcinoma after Curative Resection

Abstract: Background: The clinical features of hepatocellular carcinoma (HCC) differ in patients with and without cirrhosis. Objective: We aimed to investigate the long-term outcomes of noncirrhotic HCC patients after curative resection. Methods: We retrospectively examined 649 consecutive patients with HCC who underwent curative resection from 1996 to 2012; 387 (59.6%) were cirrhotic and 262 (40.4%) were noncirrhotic. Results: The mean age was 54.7 years, and 511 (78.7%) of the study participants were men. The most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Abstracts of the remaining 485 studies were reviewed again and 113 studies were selected for full-text review. Of these studies, 18 were qualified for this study [ 19 - 36 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abstracts of the remaining 485 studies were reviewed again and 113 studies were selected for full-text review. Of these studies, 18 were qualified for this study [ 19 - 36 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was calculated with the fraction of the risk of tumor recurrence in the cirrhosis group compared to that in the non-cirrhosis group. Original HRs of the RFS could be extracted from ten studies [ 20 , 21 , 26 , 27 , 29 - 31 , 33 , 35 , 36 ]. However, eight studies did not show their own HRs [ 19 , 22 - 25 , 28 , 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis and review indicated that portal hypertension had an adverse impact on short- and long-term outcomes for HCC patients undergoing partial hepatectomy ( 22 ). Meanwhile, liver cirrhosis was considered as one of the most important risk factors for surgical outcomes in HCC patients ( 3 , 16 , 23 , 24 ). In the present study, the 5-year OS and DFS in HCC patients with liver cirrhosis are 63.2 and 38.1%, whereas 82.7 and 59.8% for those without liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the complication rate is often high, ranging from 22% to 43% (57,58,60,62,63,(65)(66)(67)(68)70,71,73). This may be explained by the high rate of major liver resections in non-cirrhotic patients, which exceeds 50% in some series (67,68,70,72). The main complications reported were PHLF, sepsis (pneumonia, abdominal collections), bile leakage, and pleural effusion (57,63,(65)(66)(67)70,71).…”
Section: Resection Of Large Hccs In the Non-cirrhotic Livermentioning
confidence: 99%